Screening of Multipurpose Trees for Saline Vertisols and their Rioameliorative Effects - Patil, S G; Hebbara, M; Devarnavadagi, S B (Annals of Arid Zone, 2016)
Performance of 23 multipurpose trees was evaluated under saline and high water table conditions in a field trial initiated in 1989. Based upon survival, height and collar diameter observations, Casuarina equisetifolia, Acacia auriculifonnis, Dalbergia sissoo, Syzygium cuminii,Pollgamea pillllata and Glyricidiamaculata performed better under saline and high water table conditions. Moderately tolerant species identified were Albizzia amara and Pongainea pinnata. All tree species enriched the soil nutrient pool (N, P and K), organic carbon and decreased dispersibility of clays.